Impact of histological clot composition on preprocedure imaging and mechanical thrombectomy - Jeremiah N Johnson; Aditya Srivatsan; Juyu Chueh; Rose Arslanian; Matthew J Gounis; Ajit S Puri; Visish M Srinivasan; Stephen Russell Chen; Jan-Karl Burkhardt; Peter Kan (Brain Circulation, 2022)
INTRODUCTION: We studied the relationship of acute ischemic stroke (AIS) large-vessel occlusion clot composition with vessel recanalization and preprocedure imaging. SUBJECTS AND METHODS: Individual clots from AIS patients who underwent mechanical thrombectomy (MT) between September 2016 and September 2018 were examined. Clot composition was analyzed histologically through a trichrome staining and image segmentation, and the area occupied by red blood cells (RBCs), fibrin, or mixed composition was quantified. RESULTS: Forty-three patients (65.4 ± 12.7 years, 39% of females) who underwent 92 retrieval passes (mean 2.14, range 1–6) were included in this study. Fibrin (44%) occupied the greatest area, followed by mixed composition (34%) and RBCs (22%). A stent retriever was deployed in 81% of cases, 20 patients (47%) achieved first-pass efficacy (FPE) (thrombolysis in cerebral infarction [TICI] 2b-3 after first pass), 41 (95%) achieved successful revascularization (TICI 2b-3), and 21 (49%) had good outcome (modified Rankin Scale [mRS] ≤2) at 90 days. Hyperdense artery sign (HAS) on initial computed tomography was correlated with mixed clot composition (P = 0.01) and lack of fibrin content (P = 0.03). In the univariate analysis, FPE was associated with RBC clot area, atrial fibrillation, and occlusion location but not with fibrin clot area, mixed clot area, stroke etiology, thrombectomy technique, distal emboli, or 90-day mRS. In the multivariate analysis, FPE was significantly correlated with low RBC clot area (odd ratio = 0.96, confidence interval [0.92.99], P = 0.034) but not with atrial fibrillation or location. CONCLUSION: Our results suggest that HAS is correlated with mixed clot composition and lower fibrin content and that lower RBC clot composition is associated with FPE in patients undergoing MT.